Meta-Analysis: The Effect of HBM-Based Health Education on Improving Oral Health in Students - Weni Irma Suryani; Point Haryanti; Iik Sartika (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Oral health problems are an important concern in health development, one of which is caused by the vulnerability of school-age children from oral and dental health disorders. School age is an important age in the growth and physical development of children. One of them is the habit of maintaining oral and dental health. This study aims to analyze and estimate the influence of HBM-based health education on oral and dental health in students. Subject and Method: The meta-analysis was performed according to the flow of the PRISMA diagram and the PICO model. The search for articles in this study is through databases that include PubMed, Google Scholar, Science Direct and Scopus. With keywords including: